Estimation of the spawning ground of some fish species in the Nha Trang bay - Vo, Quang Van; Tran, Hoa Hong Thi; Tran, Thinh Cong; Le, Thao Thu Thi (Vietnam Journal of Marine Science and Technology, 2021)
The paper presents the results of determining the spawning grounds of some fish species in Nha Trang bay MPA, which were sampled in 9/2018, 11/2018, 5/2019 and 7/2019. The analysis results are based on the distribution of the general density and the developmental stages, analysis of decision trees from egg density, location of stations and months by CHAID (Chi-square Automatic Interaction Detector), allowing a relatively accurate estimate of the spawning ground of the red anchovy (Encrasicholina punctifer Fowler, 1938) and the species of the genus Scarus. As a result, the main spawning grounds for red anchovy were the east of Hon Rua and the northeast of Hon Tam and that of Scarus is the southwest of Hon Mun island.